Exposure of an occluded hemagglutinin epitope drives selection of a class of cross-protective influenza antibodies - Adachi, Yu; Tonouchi, Keisuke; Nithichanon, Arnone; Kuraoka, Masayuki; Watanabe, Akiko; Shinnakasu, Ryo; Asanuma, Hideki; Ainai, Akira; Ohmi, Yusuke; Yamamoto, Takuya; Ishii, Ken J.; Hasegawa, Hideki; et al. (Nature communications, 2019)
Germinal center (GC) B cells at viral replication sites acquire specificity to poorly immunogenic but conserved influenza hemagglutinin (HA) epitopes. Here, high-throughput epitope mapping of local GC B cells is used to identify conserved HA epitope selecting cross-reactive antibodies that mediate heterosubtypic protection. A distinct feature of this epitope is an occlusion in the naive trimeric HA structure that is exposed in the post-fusion HA structure to occur under low pH conditions during viral replication. Importantly, systemic immunization by the post-fusion HA antigen results in GC B cells targeting the occluded epitope, and induces a class of protective antibodies that have cross-group specificity and afford protection independent of virus neutralization activity. Furthermore, this class of broadly protective antibodies develops at late time points and persists. Our results identify a class of cross-protective antibodies that are selected at the viral replication site, and provide insights into vaccine strategies using the occluded epitope. Antibody cross-reactivity can help to prevent escape mutations from enabling viral escape, but underlying mechanisms are unclear. Here the authors identify influenza hemagglutinin epitopes that are exposed during viral replication and which result in the generation of a class of protective cross-reactive antibodies.